The research of algorithm for data mining based on fuzzy theory - Wang, A.; Li, J. (Journal of Digital Information Management, 2013)
Data Mining is a new filed in data processing research. Support Vector Machine (SVM) is one of the new methods using in data mining, which has gained great applicable success. However, there are still plenty of limitations in SVM. For example, SVM won't work if its training set contains uncertain information. In order to solve the problem presented above, this paper discusses the constraining programming of fuzzy chance and the characteristic of fuzzy classification as well as its expression methods. The algorithm for classifying Support Vector Machine is also included in this paper.
Keywords: Algorithm; Data mining; Fuzzy classification; Fuzzy linear separable; Fuzzy programming